Cortical thickness mapping to identify focal osteoporosis in patients with hip fracture - Poole, Kenneth E S; Treece, Graham M; Mayhew, Paul M; Vaculík, Jan; Dungl, Pavel; Horák, Martin; Štěpán, Jan J; Gee, Andrew H (PloS one, 2012)
BACKGROUND: Individuals with osteoporosis are predisposed to hip fracture during trips, stumbles or falls, but half of all hip fractures occur in those without generalised osteoporosis. By analysing ordinary clinical CT scans using a novel cortical thickness mapping technique, we discovered patches of markedly thinner bone at fracture-prone regions in the femurs of women with acute hip fracture compared with controls. METHODS: We analysed CT scans from 75 female volunteers with acute fracture and 75 age- and sex-matched controls. We classified the fracture location as femoral neck or trochanteric before creating bone thickness maps of the outer 'cortical' shell of the intact contra-lateral hip. After registration of each bone to an average femur shape and statistical parametric mapping, we were able to visualise and quantify statistically significant foci of thinner cortical bone associated with each fracture type, assuming good symmetry of bone structure between the intact and fractured hip. The technique allowed us to pinpoint systematic differences and display the results on a 3D average femur shape model. FINDINGS: The cortex was generally thinner in femoral neck fracture cases than controls. More striking were several discrete patches of statistically significant thinner bone of up to 30%, which coincided with common sites of fracture initiation (femoral neck or trochanteric). INTERPRETATION: Femoral neck fracture patients had a thumbnail-sized patch of focal osteoporosis at the upper head-neck junction. This region coincided with a weak part of the femur, prone to both spontaneous 'tensile' fractures of the femoral neck, and as a site of crack initiation when falling sideways. Current hip fracture prevention strategies are based on case finding: they involve clinical risk factor estimation to determine the need for single-plane bone density measurement within a standard region of interest (ROI) of the femoral neck. The precise sites of focal osteoporosis that we have identified are overlooked by current 2D bone densitometry methods.
Keywords: Female; Femur Neck; krček femuru; ženské pohlaví; Tomography, X-Ray Computed; kostní denzita; Bone Density; lidé; Osteoporosis; studie případů a kontrol; Aged, 80 and over; Densitometry; fraktury krčku femuru; Femoral Neck Fractures; Humans; denzitometrie; Case-Control Studies; Aged; Czech Republic; Česká republika; senioři nad 80 let; senioři; osteoporóza; počítačová rentgenová tomografie